Contribution to the taxonomy of the family Membracidae Rafinesque (Hemiptera: Auchenorrhyncha) in Colombia - Flórez-V, Camilo; Wolff, Marta I.; Cardona-Duque, Juliana (Zootaxa, 2015)
The Membracidae are a relatively diverse group with nearly 400 genera and 3200 species. For Colombia 93 genera and 394 species were previously known. Study of the literature and 3744 specimens deposited in ten colections in Colombia, as well as non-systematic collections and field observations done in Colombia between 2011 and 2014, led us to record 116 genera and 474 species grouped in 9 subfamilies and 23 tribes, distributed in 24 departments. Thirteen genera were new country records. In addition, 1449 records of host plants and 262 records of associated Hymenoptera were obtained from literature, the examined collections and new, non-systematic field trips. For each genus a differential diagnosis is presented, as well as notes on biology, distribution and some taxonomic comments. Illustrated keys for the genera of Colombian Membracidae and known distributional maps are given. After examination of several Anobilia species, we propose the new combinations Stilbophora flava (Tode, 1966) n. comb., Stilbophora luteimaculata (Funkhouser, 1914) n. comb., Stilbophora sagitatta (Tode, 1966) n. comb., Stilbophora silvana (Tode, 1966) n. comb., Stilbophora tripartita (Fairmaire, 1846) n. comb., and Stilbophora variabilis (Tode, 1966) n. comb.  The male of Sakakibarella sinuosa Creão-Duarte is described.